2012
DOI: 10.3109/10641963.2012.665539
|View full text |Cite
|
Sign up to set email alerts
|

Serum Gamma-Glutamyl Transferase Level Is an Independent Predictor of Incident Hypertension in Korean Adults

Abstract: The aim of our study was to assess the relationship between serum gamma-glutamyl transferase (GGT) level within the normal range and incident hypertension according to drinking and obesity status in nonhypertensive individuals. We followed up 4783 normotensive adults (mean age = 44 years) who had serum GGT levels within the normal range at baseline for 3 years. Subjects were divided into four GGT quartile groups according to their serum GGT level at baseline. The overall incidence of hypertension was 8.1%, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 19 publications
3
23
1
Order By: Relevance
“…Stojakovic et al [18] found that serum GGT activity was positively associated with male gender and markers of metabolic syndrome. Clinical and prognostic impact of GGT activity has been shown in patients with diabetes mellitus and hypertension [8,19,20]. As a result, GGT activity has an important role in the pathogenesis of cardiovascular diseases and may be used as a marker of risk of cardiovascular events [21].…”
Section: Discussionmentioning
confidence: 99%
“…Stojakovic et al [18] found that serum GGT activity was positively associated with male gender and markers of metabolic syndrome. Clinical and prognostic impact of GGT activity has been shown in patients with diabetes mellitus and hypertension [8,19,20]. As a result, GGT activity has an important role in the pathogenesis of cardiovascular diseases and may be used as a marker of risk of cardiovascular events [21].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that GGT correlates with systolic and diastolic blood pressure (69), arterial stiffness (69,70) or impaired aortic elasticity (71). Elevated but still within normal range GGT correlated with incident hypertension in drinkers and non-overweight subjects (72). Recent metaanalyses summarized the evidence linking elevated GGT level with the risk of arterial hypertension (73,74).…”
Section: Ggt and Arterial Hypertensionmentioning
confidence: 99%
“…Moreover, increased preload, as a result of increased blood pressure, contributes to the development of aneurysms (34). On the other hand, various findings indicate a correlation between serum GGT levels and high blood pressure (35). High serum GGT levels may be an indicator of increased oxidative stress in the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the maximum serum GGT levels in patients with ascending aortic dilation implies that these patients have more oxidative stress load compared to the patients with normal aortic diameter (control group). On the other hand, since the ascending aortic dilation group includes more patients with high blood pressure, this could contribute to higher serum GGT levels and increased oxidative stress (35).…”
Section: Discussionmentioning
confidence: 99%